Inventory of aliphatic hydrocarbons in a tropical mangrove estuary: a biomarker approach. Issue 4 (2nd October 2019) - Ratheesh Kumar, C. S.; Renjith, K. R.; Joseph, Manju Mary; Salas, P. M.; Resmi, P.; Chandramohanakumar, N.
Abstract: Aliphatic hydrocarbons in the sediments of the estuarine mangrove forests of Cochin region, Southwest coast of India were characterized to assess the sources of organic matter (OM) and to validate the effectiveness of the various geochemical indices to identify multiple OM sources and the complex geochemistry of these tropical coastal environments. The total concentration of the n-alkanes varied from 606.39 to 826.25 µg/g [dry weight (dw)] in mangrove sediments, to values between 230.10 and 287.67 µg/g in estuarine sediments. The n-alkane distribution in the study region indicated a strong odd over even predominance in both mangrove and estuarine sediments. Assessment using terrestrial OM indices such as Carbon Preference Index (CPI), Terrigenous Aquatic Ratio (TAR), and Terrestrial Marine Discriminant (TMD) suggested that a large fraction of OM in the mangrove sediments was derived from mangrove plant litter and a better preservation of mangrove OM in the sedimentary environment has occurred. These findings are supported by the higher content of total lipid, tannin, and lignin, as well as by the depleted δ 13 C values. Low ratios of CPI, TAR, and TMD at estuarine sites E2 and E3 indicated a mixed origin of OM. Natural or biogenic indices such as natural n-alkanes ratio (NAR), Σn-alkanes/n-C16, n-C29/n-C17, and LMW/HMW revealed that all the mangrove stations and the estuarine station E1 received OM from natural or biogenic sources, whereas a significant anthropogenic input was noticed for estuarine stations E2 and E3. Indices like Pr/Ph, Pr/n-C17, Ph/n-C18 further confirmed the mixed nature of OM accumulated under the anoxic environment.